Massachusetts General Hospital Handbook of Neurology, The, 2nd Edition - Alice W. Flaherty , Natalia S. Rost (Lippincott Williams & Wilkins, 2007)
As with the first edition, this handbook's goals are to quickly remind and update the reader. It therefore strives to be well cross-referenced, terse, and thinÃ¢â‚¬â€a pocket book should really fit in the pocket. We have tried to keep in mind that the head is actually connected to the body, and include sections on medicine and other related disciplines. The book provides a clear framework for action, without neglecting the complexity that arises when protocols are applied to real patients. Its tendency towards algorithm makes it a practical tool for non-neurologists. In the second edition we have added 20% more material, including revolutionary advances in fields like cerebrovascular disease and neuroimaging, without skimping on such common problems as migraine. We also tried to make the prose 10% less sedating than other leading neurology texts. This second edition owes its existence to Natalia Rost, who first coaxed me into starting the revision, then donated more assistance than I ever expected, and finally changed the shape of many sections byÃ¢â‚¬â€always tactfullyÃ¢â‚¬â€leading me out of conceptual errors. Drs. Beau Bruce, Andrew Chi, Tracey Cho, Edward Gilmore, Andrew Norden and Kevin Sheth at MGH made inestimable contributions in updating the book. Editors Fran Destefano, Leanne McMillan, and Angelique Amig helped greatly, as did (and does) my first editor Charley Mitchell. Many other colleagues have influenced both the book and us, including William I. (not J.) Bennett, Robert Brown, Ferdinando Buonanno, Keith Chiappa, Andrew Cole, William Copen, Bradford Dickerson, Gregory Fricchione, Michael Greene, John Growdon, Timothy Hain, John Henson, John Herman, Daniel Hoch, David Hooper, Paymon Hosseini, Farish Jenkins, Barry Kosofsky, Robert LaZebnik, Beverly Mahfuz, Jerrold Rosenbaum, Jonathan Rosand, Lee Schwamm, Katherine Sims, Lisa Townsend, Katharina Trede, Marion Stein, Shirley Wray, andÃ¢â‚¬â€always both last and firstÃ¢â‚¬â€Anne Young. Natalia and I would love to thank our husbands, Abdul Traish and Andrew Hrycyna respectively, but want to neglect that acknowledgment ritual of calling spouses Ã¢â‚¬Å“long-suffering.Ã¢â‚¬Â The book is dedicated to Walter Koroshetz, who departed this MGH lifeÃ¢â‚¬â€for the NINDSÃ¢â‚¬â€as galleys went to press. We wish we had more than words to offer in thanks for all that he has taught us by example